Microbial Population and Fermentation Characteristic in Response to Sapindus rarak Mineral Block Supplementation - S Suharti; A Kurniawati; D A Astuti; E Wina (Media Peternakan, 2010)
This experiment was conducted to evaluate the effect of supplementation with lerak extract combined with mineral block on protozoal and bacterial population, and fermentation characteristic in vitro. The experimental design was completely randomized block design with 3 treatments and 4 replications. Control diet was a substrate that consisted of concentrate, forage and feed block with ratio 50 : 48 : 2, respectively.  The treatments as a substrate were: control diet (C), C + 0.09% lerak extract, and C + 0.18% lerak extract from the total ration. Variables observed were protozoal and bacterial population, dry matter and organic matter degradability, N-NH3 and total volatile fatty acid (VFA) concentration. Data were analyzed using analysis of variance (ANOVA). The result showed that there were no significant effect (P>0.05) for all parameter measured with lerak extract supplementation up to 0.18% in the presence of mineral block. However, supplementation of lerak extract 0.18% only slightly reduced protozoal numbers but tended to increase bacterial numbers. Dry matter and organic matter degradability and concentration of N-NH3 were similar among treatments. Volatile fatty acids profile changed which propionate tended to increase and acetate tended to decrease and ratio of acetate to propionate tended to decrease. In conclusion, addition of lerak extract up to 0.18% from total ration in the presence of mineral block  was not yet effective to depress protozoal population, but could modify fermentation characteristic in vitro.